The Role of Smart Cities and Social Connectivity in Advancing the Smart Economy - Riyadhusholihah Riyadhusholihah; Haryono Umar (Universitas Muhammadiyah Ponorogo, 2027)
The emergence of smart cities represents a transformative shift in urban development, integrating digital technologies, data-driven governance, and sustainable infrastructure to enhance quality of life and economic efficiency. This article explores how smart city initiatives are reshaping business dynamics and driving the growth of the smart economy. By leveraging technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics, smart cities enable new business models, optimize operational efficiency, and support innovation ecosystems. The paper also highlights the critical role of public–private partnerships, regulatory frameworks, and digital infrastructure in creating an economic environment that is responsive, adaptive, and inclusive. Through a multidisciplinary analysis, this study reveals the interconnection between urban intelligence and economic competitiveness, offering strategic insights for policymakers, business actors, and urban planners. Ultimately, smart cities do not merely transform how cities operate they also redefine how businesses compete and collaborate in the digital age. However, this study has limitations; therefore, future research should expand the scope and methodology to extend the findings. Keywords: Smart City; Business Dynamics; Smart Economy; Urban Innovation; Digital Transformation; Economic Competitiveness;